Acute Toxicological and Histopathological Elucidation of Rheum emodi Rhizome Extract to Demonstrate Antidiabetic Activity in Alloxan-induced Diabetic Rats - Radhika, Ravindran; Ramadas, Dinesha; Ragavan, Baliah; Sudarsanam, Dorairaj; Kameshwar, Vivek H. (Current Bioactive Compounds, 2021)
Background: Rheum emodi has been used traditionally to treat diabetes in India. The study was designed to elucidate the effect of 75% ethanolic extract of R. emodi (rhizome) (EE-ReR) and its isolated compounds like emodin and chrysophanol on alloxan-induced diabetic rats, and to check its antidiabetic efficacy. Acute toxicological and histopathological studies were also assessed. Methods: Experimental rats were divided into six groups, with each group consisting of 6 rats. EEReR and its compounds emodin and chrysophanol were given orally for 30 days. Results: The experimental rats were sacrificed after 30 days by cervical dislocation. The renal profile and lipid parameters were determined. Histopathological changes in liver, kidney and pancreas were examined in EE-ReR treated group. EE-ReR was fed orally to diabetic rats, which resulted in a decline in the fasting blood glucose, total cholesterol, free fatty acids, creatinine, urea levels, and a rise in the insulin levels was observed almost in the normal range, in the rats which were fed with the extract. Histopathological studies of pancreas, kidney, and liver in diabetic rats revealed that the treated group of rats showed normal regeneration of islets cells. Acute toxicological studies revealed that the extract is safe up to 2000 mg/kg body weight of extract fed orally. Conclusion: These findings suggested a possible protective method to prevent damage of the internal organs by the R. emodi and its compounds like emodin and chrysophanol, and elevate insulin production during high blood glucose levels without any acute toxicological effect.
Keywords: kidney function